IMF Survey : Volume 28, Issue 20. (IMF Survey; IMF Survey ;, 1999)
Following are edited extracts of an address by IMF Managing Director Michel Camdessus at the Konrad Adenauer Foundation in Frankfurt on October 11. The full text is available on the IMF's website (www.imf.org).